MAMOPLASTIA DE AUMENTO PÓS-MASTECTOMIA SUBCUTÂNEA COM INCISÃO TRANSAREOLOMAMILAR PELA TÉCNICA DE PITANGUY - Bottega, Caroline; Zambra, Melissa; Fockink, Luisa; Oliveira, Vanessa C. d. (Salão do Conhecimento, 2013)
Resumo